Morphological, geochemical and mineralogical studies of two soil profiles developed on the itabirites of Ntem Complex, southern Cameroon - Odigui Ahanda, Damien Henri; Ndzana, Georges Martial; Bekoa, Etienne; Abossolo-Angue Abane, Monique; Bitom, Lucien Dieudonné (Journal of African earth sciences (1994), 2019)
Itabirite-related ferrallitic soils in the humid tropical zone of southern Cameroon have proven economic and scientific interests. However, they have received very little attention. The morphological, mineralogical and geochemical features of two soil profiles (TCN in Nkout and NT in Anyouzok) with significant morphological differences and developed on itabirite in the Ntem Complex of southern Cameroon were studied using macroscopic and microscopic observations, conventional X-ray diffraction (XRD), X-ray fluorescence (XRF) spectrometry and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) analyses. The two profiles have similar sets of horizons including a lower weathering unit, a ferruginous and a loose upper units. However, TCN has a saprolite horizon above the saprock and numerous platy ferruginous concretions. The two profiles have similar mineralogical composition with the predominance of hematite, goethite, quartz and magnetite and a low concentration of kaolinite and gibbsite. The geochemical composition is characterized by the dominance of Fe2O3t (58.90–90.76 wt %) and SiO2 (5.63–38.45 wt %) both showing opposite trends across the profiles. These observations suggest that oxidation and dissolution were the dominant geochemical processes during the formation of the profiles. The positive Ce anomalies (Ce/Ce*: 1.12 to 2.27) and negative Eu anomalies (Eu/Eu*: 0.59 to 0.99) are indicators of oxidations coupled with mobile elements leaching in the profiles. The morphological differences between the two profiles are probably due to differences in weathering conditions which led to the development of a thick oxidized iron ore deposit in Nkout compared to Anyouzok. •The geochemical composition of itabirite-related ferrallitic soils is characterized by the dominance of Fe2O3 and SiO2.•Ferrallitic soils on itabirites show a mineralogical composition marked by very low contents of kaolinite and gibbsite.•The features of the studied profiles characterise the environmental influence on supergene weathering and pedogenesis.•The combined action of the parent rock lithology and the geomorphology led to different types of enriched iron ore bodies.